Clima laboral de los trabajadores del área de maquinaria del Gobierno Autónomo Descentralizado del cantón Yantzaza. Perspectiva del Trabajador Social. - Sarango Alejo, Diana Mairene (2024)
Work climate is a key factor within organizations, companies, or institutions, given that it is present in the environment where workers develop by maintaining an adequate work climate, it is possible to achieve the objectives proposed by the institutions; otherwise, discrepancies are present that difficult effectively carry out its work. The present research was developed with the aim of evaluating from a Social Work point of view, the working climate of the workers in the machinery area of the Autonomous Decentralized Government of Yantzaza Canton, through a mixed approach with a non-experimental and transversal design, with a descriptive scope allowing the analysis of how the working climate is through the C-SPC working climate scale aimed at 32 workers belonging to the machinery area; also, through an interview with the social worker and the chief of the collaborators. The results obtained reflect that the intervention of the social worker in this area is scarce, moreover, the existence of an inadequate working climate where the most difficult dimensions are communication and personal fulfilment; however, the dimensions of work involvement, supervision and working conditions are highlighted as they demonstrated to remain in a favorable score. On the other hand, an intervention plan was realized based on strategies aimed at counteracting the problems found that directly affect the work climate. In conclusion, the work climate in the machinery area is regular, for this reason, the intervention of the social worker is very important, the follow-up and the application techniques are the fundamental pillars to improve the environment of the whole work team.